Real Business in China. - Britton, Michael (Deutscher Verkehrs-Verlag, 2005)
The outsourcing of production to the lower cost areas of the world by North American, European, and Japanese companies has fueled China s relentless rise as a manufacturing and trading superpower. Some analysts believe that growth has been too fast and the Chinese economy is at risk of overheating citing rising inflation in the largest cities. In general, however, the majority view is that China s economy is solidly based and growth in GDP should continue well for a minimum of five years. The economy is well balanced with demand for raw materials, investment goods and luxury goods matching exports. difu
Keywords: Wirtschaftsentwicklung; Wirtschaftspolitik; Energie; Verkehr; Güterverkehr; Verkehrsinfrastruktur; Hafenanlage; Schiffbauindustrie; Binnenschiffsverkehr; Schienengüterverkehr; Straßengüterverkehr; Logistik; Transportmittel; Wirtschaftsverkehr